Predicting E-Cigarette Adoption Among University Students: A Theory of Planned Behavior Approach in a Collectivist Context - Siti Fatimah; Chandra Kartika Dewi; Adila Nur'aini Az Zahra; Muhammad Yasin Al-Fath (Al-Hijrah Indonesia, 2026)
E-cigarette use has become an increasingly prevalent trend among university students, accompanied by ongoing debates regarding its long-term health effects. This trend is linked to the perception that e-cigarettes contain lower levels of nicotine and otherharmful substances compared to conventional tobacco cigarettes. This study aimed to examine the factors influencing students' adoption of e-cigarettes by applying the Theory of Planned Behavior(TPB). The research was conducted among students at UIN Sunan KalijagaYogyakarta. Data were collected via an online survey distributed through the university's academic system, with respondents recruited through accidental and snowball sampling. A total of 105 students completed the questionnaire and were included in the analysis. The results showed that the TPB model explained only 12.1% of the variance in students' intention to adopt e-cigarettes, a notably low value indicating the influence of factors beyond the standard TPB constructs. Attitude toward behavior (β= 0.251) and perceived behavioral control (β= 0.169) were positively associated with intention, whereas subjective norm was negatively associated. This finding indicates that social referents tended to discourage rather than promote the adoption of e-cigarettes. The attitude toward behaviorconstruct was primarily driven by items reflecting social acceptance rather than health-risk perceptions. These findings suggest that students' adoption of e-cigarettes as an alternative to conventional tobacco cigarettes is influenced more by social factors than by perceptions of reduced health risks